A method for identifying three-dimensional rock blocks formed by curved fractures. (April 2015) - Zheng, Yinhe; Xia, Lu; Yu, Qingchun
Abstract: Identifying blocks formed by various fractures is important in rock engineering. Most studies focus mainly on blocks formed by planar fractures whereas curved fractures are rarely considered. However, large fractures observed in the field are often curved. This paper presents a new method for identifying rock blocks formed by both curved and planar fractures based on the element-block-assembling approach, in which the study domain is divided into numerous tetrahedral subdomains under the constraint of curved fractures and the subdomains are further decomposed into element blocks by extended planar fractures. When the fractures are restored to finite dimensions, the element blocks are combined and the subdomains are assembled to form complex blocks. The combination of the two subdomains is skipped if and only if their common facet lies on a curved fracture. A computer program was implemented based on the method introduced in this study and the verification examples indicated that this method could effectively handle both convex and concave blocks.